A STUDY ON CORPORAL PUNISHMENT IN SCHOOLS AT SIVAKASI - Kalaivani (International Journal of Research -GRANTHAALAYAH, 2016)
Corporal punishment has been classified as an act of violence and abuse on children. Strictly defined ‘corporal punishment’ is the infliction of pain intended to change a person’s behaviour or to punish them. Though it mainly refers to physical pain either through hitting or forcing the child to sit /stand in uncomfortable positions; an evolving definition also includes within its ambit wrongful confinement, verbal insults, threats and humiliation, which are used with impunity and in utter disregard to the law of land and principles of learning. Children due to fear are often silent and submit to violence without questioning. They sometimes show signs of deep hurt in their behavior but this often goes unnoticed, perpetuating further violence on them. Corporal punishment not only affects the emotional behaviour and academic performance of a child, but also leads to reduction in self-esteem and dignity of child.